The impact of weather condition to construction project in Malaysia - Nur Shahirah, Abu Hassan Asaari (2018)
Weather conditions in Malaysia are the cause of delay in construction project and affect parties involved with period and cost problems. Due to uncertain weather and severe impact on all construction activities that will be limited by losses that may be attributable to reduced labor productivity due to interruption of an activity. Weather conditions that can be linked are rain, heat and extreme winds condition as Malaysia is known as a hot and humid throughout all year. Delayed by weather can be mitigated when impacts and means of overcoming during construction are identified. The objective of this study is to identify the main effects of the weather affecting the delay in the construction project and the way it is used to solve the problem. This study is based on literature review and information collection through surveys. From the survey, this study presents the results of the study to determine and assess the major effects of the cause of the delay caused by the weather and the way they handle it. This survey is distributed to contractors, consultants, owners who are randomly assigned. Relative importance index (RII) is used to create average scores and ranking for analysis and conclusions. The direct and indirect effects of weather events on logistics, areas, processes or productivity, employees and finances are discussed in detail. Direct and indirect effects of weather and climate change include damage to equipment and areas due to higher temperatures and increased rainfall, with delayed costs and increased cost to the project.